Factors that influencing credit card spending behavior among staff in Universiti Kuala Lumpur (UniKL) at Sultan Ismail Road, Kuala Lumpur / Nor Aizuddin Nor Aziz and Izzah Azri Hamidon - Nor Aziz, Nor Aizuddin; Hamidon, Izzah Azri (Faculty of Business and Management, 2014)
This research is to study several factors which is age, income, bank policies, attitude towards money and psychological factor as the variable that may influence the credit card spending behavior among the staff in Universiti Kuala Lumpur (UniKL). This research helps to determine the pattern of credit card spending behavior and to identify the factors that influence the credit card spending behavior. The variable is help to determine the most influencing factor towards the credit card spending behavior. The data originally consist of 5-dimension data analysis which include descriptive analysis, frequencies analysis, person correlations coefficient analysis, reliability analysis and multiple regression analysis. This model helps to evaluate the factors that influence the credit card spending behavior.